STUDY OF THE PHOTODEGRADATION OF METHYLENE BLUE: POTENTIAL APPLICATION IN ANTIBACTERIAL PHOTODYNAMIC THERAPY (CIPEEX, 2023)
Photodynamic Therapy (PDT) is an ancient technique that uses light as a therapeutic agent, with roots in ancient civilizations such as Egypt, India, and China, although its scientific understanding developed in the early 20th century. Niels Finsen, a Danish physician, innovated by applying red and ultraviolet light in the treatment of smallpox and cutaneous tuberculosis, earning him the Nobel Prize in 1903. PDT, introduced by von Tappeiner, is based on the use of light-activated photosensitizers to damage target cells, receiving FDA approval to treat esophageal cancer in 1995. The photochemotherapy technique combines photosensitizers with light in the tissues where they are present, with applications dating back to ancient times, such as the use of psoralens by indigenous people to treat vitiligo. PDT has found applications in various medical fields, such as cancer, dermatology, ophthalmology, dentistry, and more. Methylene blue is a common photosensitizer in PDT, generating reactive oxygen species when activated by light, being used in the treatment of cancer and infections, as well as improving tissue visualization in medical procedures. In this work, we studied the photodegradation of methylene blue when irradiated with different energies at a wavelength of 661 nm.
Keywords: Photodynamic therapy; Methylene Blue; UV-VIS spectrophotometry